A case study of two participating companies on the impact of national dual training system (NDTS) implementation on teaching strategies - Tokeran, Mohd Faizal (2016)
The implementation of National Dual Training System (NDTS) in Malaysia requires the new form of teaching strategies which based on work process knowledge. Therefore, the new teaching and learning environment which focuses on work-process-orientation needs to be designed appropriately to meet the ever changing work process in the industry. The main objective of this study is to explore and discover the existing practice of development and application of Learn and Work Assignment (LWA) and other relevant training materials. The study adopted a mixed method of qualitative and quantitative research and the data collection were interviews, document reviews and observations. In order to investigate the real situation, two companies which were involved in transportation industry were selected as a study case. The finding leads to the determination of areas and characteristics of work-process-orientation teaching strategies to be embraced in teaching strategies thus the level of compliances for participating companies can be evaluated. For the development stage, the study found that the work-process-orientation in four areas which are; (i) appropriate use of development methodology, (ii) personnel involved, (iii) description of L WA documentation, and (iv) classification of complexity and difficulty were at high degree of compliance. With respect to the work-process-orientation implementation, three areas have been identified; (i) consideration of didactical approach, (ii) methodology of training, and (iii) role of coach and trainer. The study also discovered that the workprocess-orientation on the implementation stage or teaching process achieved a high degree of compliance. The work-process-orientation compliance assessment scheme which was developed and used in this study can be benefited for assessing the extent of work-process-orientation in teaching strategies at the NDTS participating companies.